Preparation method of smokeless easy-to-sinter environment-friendly converter large-surface repair material

By preparing a large-side repair material for environmentally friendly converter containing leather sand, magnesium-aluminum bonding agent and sintering additive, the problem of black smoke and pollution generated by traditional repair materials is solved, and smoke-free, easy sintering and environmentally friendly repair is achieved. The results have improved workers' health and environmental safety.

CN119176710APending Publication Date: 2024-12-24SHANXI LUWEIBAO TAIGANG REFRACTORIES CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411382823.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

During the use of existing converter large surface repair materials, a large amount of black smoke will be produced, polluted the environment, and the repair time will be long, which will cause harm to workers' health and the environment, and will violate the idea of ​​green development.

Method used

60-70% 0-5mm particle size peel sand, 14-18% 200 mesh peel sand, 0-8% 325 mesh binding agent, 3-5% 320 mesh silicon micro powder, 0-2% 200 mesh Aluminum powder, 3-5% 325 mesh α-alumina powder, 0-6% 200 mesh sintering additive and 0-0.22% water reducing agent, smoke-free preparation by crushing, dry mixing, molding, drying and heat treatment Eco-friendly converter with large surface repair material for easy sintering.

Benefits of technology

It realizes a smoke-free, environmentally friendly and low-cost repair process, shortens the sintering time, improves the density and service life of the material, and reduces pollution and health risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176710A_ABST
    Figure CN119176710A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of repairing materials, and particularly relates to a preparation method of a smokeless easy-to-sinter environment-friendly converter large-surface repairing material which comprises the following components: 60-70 parts of leather sand with the particle size of 0-5 mm; 14-18 parts of leather sand with the particle size of 200 meshes; 0-8 parts of a binding agent with the particle size of 325 meshes; 3-5 parts of silica powder with the particle size of 320 meshes; 0-2 parts of aluminum powder with the particle size of 200 meshes; 3-5 parts of alpha-alumina powder with the particle size of 325 meshes; 0-6 parts of a sintering aid with the particle size of 200 meshes; according to the present invention, the main raw material is the leather sand, such that the large surface repair material can be easily sintered and has the low cost compared with the currently used large surface repair material using the high-purity magnesia as the main raw material under the same condition; the binding agent is a magnesium-aluminum binding agent which is more environmentally friendly than a traditional binding agent, no irritant gas is generated in the using process, no combustible matter exists in the binding agent, and the sintering time is greatly shortened. The water reducing agent is a high-efficiency water reducing agent, so that the water consumption is reduced, the volume density is effectively increased, and the service life is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of repair materials, and in particular relates to a method for preparing a smokeless, easy-to-sinter, environment-friendly converter large-surface repair material. Background Art

[0002] In the early 20th century, my country's converter large-surface repair materials were mainly composed of dolomite as aggregate and tar as binder. Although it has the advantages of low price and can be mass-produced, the sintering time is too long, the bonding is extremely unstable, and the pollution is serious. At the end of the 20th century, asphalt and dolomite were mixed for repair, but abnormal damage such as collapse, inversion, inability to repair or excessive corrosion often occurred. Subsequently, the requirements for water-resistant base energy increased, and the binder was changed from asphalt to asphalt powder and dolomite to magnesia. Although the defect of solidification into blocks was overcome and it had high bonding strength, the sintering time was too long and the sintering was insufficient, resulting in serious waste. In the 21st century, my country's converter large-surface repair materials are mainly carbon-magnesium repair materials with tar, asphalt, etc. as binders. However, during use, toxic organic volatiles and a large amount of black smoke will be generated, and the repair time is very long, which will not only cause great harm to the health of workers, but also pollute the environment. The construction is not easy to operate, which is not conducive to the benefits of steel mills, has a great impact on the production rhythm of steel mills, and reduces steelmaking efficiency. At present, my country's research on large-surface repair materials for converters using inorganic materials as binders is mostly based on amorphous dry magnesium materials. After repair, it was found that the corrosion resistance of the converter lining was still poor, which also affected the service life of the converter.

[0003] At present, most of the materials used are traditional large-surface repair materials for converters. They use asphalt and phenolic resin as binders, benzene substances as flow promoters, and magnesia as the main raw material. They are an amorphous magnesium-carbon refractory material. Although they have good fluidity, they will produce a lot of black smoke during the repair process, polluting the environment. The repair time is long, and it also has serious harm to the health of workers. It is not conducive to improving people's sense of happiness, and it also has an adverse effect on the development of converter steelmaking, which is inconsistent with the green development concept of heavy industry.

[0004] Therefore, the development of environmentally friendly converter reinforcement materials has become the focus of research. The "water-based" converter large surface repair material uses water and water reducing agent as the dispersion medium, while the converter large surface repair material with asphalt and resin as the binder uses solvent as the dispersion medium. The advantages of "water-based" rubber products are: no solvent, non-flammable, high solid content, environmentally friendly, non-toxic, and no harmful gases are generated during sintering.

[0005] Therefore, it is necessary to prepare a smokeless, easy-to-sinter, environmentally friendly converter large-surface repair material to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large-surface repair material, aiming to solve the problem that currently, most of the traditional converter large-surface repair materials used are amorphous magnesium-carbon refractory materials with asphalt and phenolic resin as binders, benzene substances as flow promoters, and magnesia as the main raw material. Although the material has good fluidity, it will produce a large amount of black smoke during the repair process, polluting the environment. The repair time is long, it also has serious harm to the health of workers, is not conducive to improving people's sense of happiness, and has an adverse effect on the development of converter steelmaking, which is inconsistent with the green development concept of heavy industry.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large surface repair material, comprising the following components:

[0008] 60-70 parts of leather sand with a particle size of 0-5 mm;

[0009] 14-18 parts of leather sand with a particle size of 200 mesh;

[0010] 0-8 parts of a binder with a particle size of 325 mesh;

[0011] 3-5 parts of 320 mesh silica powder;

[0012] 0-2 parts of aluminum powder with a particle size of 200 mesh;

[0013] 3-5 parts of α-alumina powder with a particle size of 325 mesh;

[0014] 0-6 parts of sintering aid with a particle size of 200 mesh;

[0015] 0-0.22 parts of water reducing agent.

[0016] As a preferred method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large-surface repair material of the present invention, the skin sand is low-purity fused magnesia sand, and the magnesium oxide content is between 92% and 95%.

[0017] As a preferred method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large surface repair material of the present invention, the particle size of the skin sand is 5-3mm 3-1mm 1-0mm or 5-3mm 3-0mm.

[0018] As a preferred method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large surface repair material of the present invention, the binder is a magnesium-aluminum binder, the magnesium oxide content is between 55% and 56%, and the aluminum oxide content is between 41% and 42%.

[0019] As a preferred method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large surface repair material of the present invention, the silicon dioxide content in the silicon micropowder is above 94%.

[0020] As a preferred method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large surface repair material of the present invention, the α-alumina powder is industrial alumina, and the alumina content is above 98%.

[0021] As a preferred method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large surface repair material of the present invention, the sintering aid is one or more of iron oxide or calcium oxide.

[0022] As a preferred method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large surface repair material of the present invention, the water reducing agent is one or more of TB802, TB803 or NF8010.

[0023] A method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large-surface repair material, characterized in that it comprises the following steps:

[0024] A raw material crushing, crushing large pieces of raw materials and screening them into corresponding particle sizes.

[0025] B Dry mixing: prepare leather sand of different particle sizes, binder, silica powder, aluminum powder, α-alumina powder, sintering aid and water reducer according to the proportion, then pour the 0-5mm leather sand aggregate into the mixing equipment, mix evenly, then pour in the powder in turn and mix evenly.

[0026] C Sampling test: take a certain amount of mixed material, add water and stir, put it into a triple test mold for vibration molding, demoulding, drying, heat treatment, and test its physical indicators, compressive strength, flexural strength, bulk density and apparent porosity.

[0027] D. Packaging: Pack the prepared smokeless, easy-to-sinter, environmentally friendly converter large surface repair material and store it in a dry and cool finished product workshop.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The main raw material of the present invention is leather sand, which is easier to sinter under the same conditions than the currently used large-surface repair material with high-purity magnesia as the main raw material and has lower cost.

[0030] (2) The binder of the present invention is a magnesium-aluminum binder, which is more environmentally friendly than traditional binders, and no irritating gas is generated during use. In addition, there is no combustible material in the binder, which greatly reduces the sintering time.

[0031] (3) The water reducing agent of the present invention is a high-efficiency water reducing agent, which reduces the water consumption, effectively increases the volume density, and prolongs the service life.

[0032] (4) The combined use of the sintering aid and various additives in the present invention effectively reduces the sintering temperature of the large-surface repair material, making the material more dense. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0034] Figure 1 It is a schematic diagram of the components of the converter large surface repair material of the present invention;

[0035] Figure 2 The present invention is a schematic diagram of the production process of the converter large surface repair material. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] See also Figure 1-2 The present invention provides the following technical solution: a method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large-surface repair material, comprising the following components:

[0038] 60-70 parts of leather sand with a particle size of 0-5 mm;

[0039] 14-18 parts of leather sand with a particle size of 200 mesh;

[0040] 0-8 parts of a binder with a particle size of 325 mesh;

[0041] 3-5 parts of 320 mesh silica powder;

[0042] 0-2 parts of aluminum powder with a particle size of 200 mesh;

[0043] 3-5 parts of α-alumina powder with a particle size of 325 mesh;

[0044] 0-6 parts of sintering aid with a particle size of 200 mesh;

[0045] 0-0.22 parts of water reducing agent.

[0046] Preferably: the skin sand is low-purity fused magnesia sand, and the magnesium oxide content is between 92% and 95%. The grain size of the skin sand is 5-3mm 3-1mm 1-0mm or 5-3mm 3-0mm. The binder is a magnesium-aluminum binder, and the magnesium oxide content is between 55% and 56%, and the aluminum oxide content is between 41% and 42%. The silicon dioxide content in the silicon micropowder is above 94%. The α-alumina powder is industrial alumina, and the aluminum oxide content is above 98%. The sintering aid is one or more of iron oxide or calcium oxide. The water reducer is one or more of TB802, TB803 or NF8010.

[0047] The following Examples 1, 2, and 3 are all prepared in this manner: A method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large-surface repair material comprises the following steps:

[0048] A raw material crushing, crushing large pieces of raw materials and screening them into corresponding particle sizes.

[0049] B Dry mixing: prepare leather sand of different particle sizes, binder, silica powder, aluminum powder, α-alumina powder, sintering aid and water reducer according to the proportion, then pour the 0-5mm leather sand aggregate into the mixing equipment, mix evenly, then pour in the powder in turn and mix evenly.

[0050] C Sampling test: take a certain amount of mixed material, add water and stir, put it into a triple test mold for vibration molding, demoulding, drying, heat treatment, and test its physical indicators, compressive strength, flexural strength, bulk density and apparent porosity.

[0051] D. Packaging: Pack the prepared smokeless, easy-to-sinter, environmentally friendly converter large surface repair material and store it in a dry and cool finished product workshop.

[0052] Factory usage: Pour the prepared raw materials into the mixing equipment, add appropriate amount of water and mix evenly, then after the molten steel is poured out of the converter, quickly pour in the mixed large-surface repair material, and use the gap between the converter and the residual heat for repair.

[0053] Embodiment 1:

[0054] 21 parts of leather sand with a particle size of 0-5mm, 21 parts of leather sand with a particle size of 0-5mm, 28 parts of leather sand with a particle size of 0-5mm, 9 parts of leather sand with a particle size of 200 mesh, 7 parts of binder with a particle size of 325 mesh, 3 parts of silicon micropowder with a particle size of 320 mesh, 5 parts of aluminum powder with a particle size of 200 mesh, 4 parts of α-alumina powder with a particle size of 325 mesh, 2 parts of sintering aid with a particle size of 200 mesh, and 0.12 parts of water reducer.

[0055] The data measured after heat treatment are as follows: the flexural strength is 8.55MPa after 3h at 1600℃, and the maximum volume density is 2.95g / cm3 , the minimum apparent porosity is 14.0%.

[0056] Embodiment 2:

[0057] 15 parts of leather sand with a particle size of 0-5mm, 21 parts of leather sand with a particle size of 0-5mm, 27 parts of leather sand with a particle size of 0-5mm, 16 parts of leather sand with a particle size of 200 mesh, 5 parts of binder with a particle size of 325 mesh, 3 parts of silicon micropowder with a particle size of 320 mesh, 5 parts of aluminum powder with a particle size of 200 mesh, 4 parts of α-alumina powder with a particle size of 325 mesh, 4 parts of sintering aid with a particle size of 200 mesh, and 0.17 parts of water reducer.

[0058] The data measured after heat treatment are as follows: the flexural strength is 9.01MPa after 3h at 1600℃, and the maximum volume density is 3.01g / cm 3 , the minimum apparent porosity is 13.2%.

[0059] Embodiment 3:

[0060] 15 parts of leather sand with a particle size of 0-5mm, 21 parts of leather sand with a particle size of 0-5mm, 27 parts of leather sand with a particle size of 0-5mm, 18 parts of leather sand with a particle size of 200 mesh, 3 parts of binder with a particle size of 325 mesh, 3 parts of silicon micropowder with a particle size of 320 mesh, 1 part of aluminum powder with a particle size of 200 mesh, 4 parts of α-alumina powder with a particle size of 325 mesh, 3 parts of sintering aid with a particle size of 200 mesh, and 0.22 parts of water reducer.

[0061] After 3 hours of heat preservation at 1600℃, the room temperature flexural strength is 11.05MPa, and the room temperature compressive strength is 112.3MPa. The maximum volume density is 3.028g / cm 3 , the apparent porosity is 11%. Used in 180T converter, each furnace repair needs 1.5-2T of environmentally friendly converter large surface repair material, the average service life is about 30 times, the amount of water added is 10wt%, the spreading time is 40-120s, the sintering time is 12-20min, and the repair thickness is between 30-50mm. It has achieved the industrial use effect of low cost, high performance and reduced pollution.

[0062] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A smokeless, easy-to-sinter, environmentally friendly converter large surface repair material, characterized in that: Includes the following components: 60-70 parts of leather sand with a particle size of 0-5 mm; 14-18 parts of leather sand with a particle size of 200 mesh; 0-8 parts of a binder with a particle size of 325 mesh; 3-5 parts of 320 mesh silica powder; 0-2 parts of aluminum powder with a particle size of 200 mesh; 3-5 parts of α-alumina powder with a particle size of 325 mesh; 0-6 parts of sintering aid with a particle size of 200 mesh; 0-0.22 parts of water reducing agent.

2. The smokeless, easy-to-sinter, environmentally friendly converter large surface repair material according to claim 1, characterized in that: The skin sand is low-purity fused magnesia sand, and the magnesium oxide content is between 92% and 95%.

3. The smokeless, easy-to-sinter, environmentally friendly converter large surface repair material according to claim 1, characterized in that: The grain size of the leather sand is 5-3mm 3-1mm 1-0mm or 5-3mm 3-0mm.

4. The smokeless, easy-to-sinter, environmentally friendly converter large surface repair material according to claim 1, characterized in that: The binder is a magnesium-aluminum binder, the magnesium oxide content is between 55% and 56%, and the aluminum oxide content is between 41% and 42%.

5. The smokeless, easy-to-sinter, environmentally friendly converter large surface repair material according to claim 1, characterized in that: The silicon dioxide content in the silicon micropowder is above 94%.

6. The smokeless, easy-to-sinter, environmentally friendly converter large surface repair material according to claim 1, characterized in that: The α-alumina powder is industrial alumina, and the alumina content is above 98%.

7. The smokeless, easy-to-sinter, environmentally friendly converter large surface repair material according to claim 1, characterized in that: The sintering aid is one or more of iron oxide and calcium oxide.

8. The smokeless, easy-to-sinter, environmentally friendly converter large surface repair material according to claim 1, characterized in that: The following steps are involved: The water reducing agent is one or more of TB802, TB803 or NF8010.

9. A method for preparing a smokeless, easy-to-sinter, environmentally friendly converter large surface repair material, comprising any one of claims 1 to 8, characterized in that: The following steps are involved: A raw material crushing, crushing large pieces of raw materials and screening them into corresponding particle sizes; B Dry mixing: prepare leather sand of different particle sizes, binder, silica powder, aluminum powder, α-alumina powder, sintering aid, and water reducer according to the proportion, then pour the leather sand aggregate of 0-5mm into the mixing equipment, mix evenly, then pour the powder materials in turn and mix evenly; C Sampling test: take a certain amount of mixed materials, add water and stir, put them into a triple test mold for vibration molding, demoulding, drying, heat treatment, and test their physical indicators, compressive strength, flexural strength, bulk density and apparent porosity; D. Packaging: Pack the prepared smokeless, easy-to-sinter, environmentally friendly converter large surface repair material and store it in a dry and cool finished product workshop.

Citation Information

Patent Citations

  • Hot patching material for large face of converter

    CN101913893A

  • Self-flow type large-area batching mix for revolving furnace and methods for preparing and using self-flow type large-area mix

    CN102807381A

  • Water-based large fabric for converter and preparation method of water-based large fabric

    CN116751067A

  • Manufacturing method and application of water-based environment-friendly converter large-surface repairing material

    CN118184315A

  • Hydraulic composition and paste, mortar and concrete using it

    JP2002137954A